Mononeuritis multiplex following immune checkpoint inhibitors in malignant pleural mesothelioma - Farina, Antonio; Escalere, Manon; Dion, Matthias; Moussy, Martin; Pegat, Antoine; Villagrán-García, Macarena; Devic, Perrine; Lamiral, Anaïde; Seyve, Antoine; Aure, Karine; Wang, Adrien; Gorza, Lucas; et al. (Frontiers in Neurology, 2024)
Introduction Mononeuritis multiplex is frequently related to vasculitic neuropathy and has been reported only sporadically as an adverse event of immune checkpoint inhibitors. Methods Case series of three patients with mononeuritis multiplex—all with mesothelioma—identified in the databases of two French clinical networks (French Reference Center for Paraneoplastic Neurological Syndromes, Lyon; OncoNeuroTox, Paris; January 2015–October 2022) set up to collect and investigate n-irAEs on a nationwide level. Results Three patients (male; median age 86 years; range 72–88 years) had pleural mesothelioma and received 10, 4, and 6 cycles, respectively, of first-line nivolumab plus ipilimumab combined therapy. In patient 1, the neurological symptoms involved the median nerves, and in the other two patients, there was a more diffuse distribution; the symptoms were severe (common terminology criteria for adverse events, CTCAE grade 3) in all patients. Nerve conduction studies indicated mononeuritis multiplex in all patients. Peripheral nerve biopsy demonstrated necrotizing vasculitis in patients 1 and 3 and marked IgA deposition without inflammatory lesions in patient 2. Immune checkpoint inhibitors were permanently withdrawn, and corticosteroids were administered to all patients, leading to complete symptom regression (CTCAE grade 0, patient 2) or partial improvement (CTCAE grade 2, patients 1 and 3). During steroid tapering, patient 1 experienced symptom recurrence and spreading to other nerve territories (CTCAE grade 3); he improved 3 months after rituximab and cyclophosphamide administration. Discussion We report the occurrence of mononeuritis multiplex, a very rare adverse event of immune checkpoint inhibitors, in the three patients with mesothelioma. Clinicians must be aware of this severe, yet treatable adverse event.